Are the Enclaves on the Same Boat? An Investigation on the Development Indicators of Dahagram–Angarpota of Bangladesh. (September 2021) - Misu, Farjana; Khatun, Mst. Asma; Islam, Mohammad Amirul
Enclaves are the most distressed areas in the world where the ray of development hardly reaches. This study aims to evaluate the progress in the development in Dahagram–Angarpota enclave of Bangladesh after the initiation of 24-h open corridor access through the Indian territory in 2011. The study reveals that after 24-h open access through the corridor, the enclave achieved substantial positive changes in all the five indicators, namely, economic, social and infrastructural, technological, health and demographic indicators. However, the achievement in the four influential factors of development such as income, wealth, poverty and food security are still below the national level. Binary logistic regression model identified a positive change in income–wealth index of households through the changes in corridor access, education, electricity supply, number of livestock and involvement with micro credit. In the process of raising income–wealth, achieving food security and alleviating poverty, this study has suggested some policy recommendations that would guide different development programmes in the area.